Attachment as A Predictor of University Adjustment Among Freshmen: Evidence from A Malaysian Public University - Wider, Walton; Mustapha, Mazni; Halik, Murnizam; Bahari, Ferlis (Universiti Utara Malaysia Press, 2017)
Purpose - Building upon attachment theory and emerging theory, the current study was aimed at examining the effect of peer attachment in predicting adjustment to life in university among freshmen in a public university in East Malaysia. Furthermore, it sought to examine the influence of gender and perceived-adult status as moderators of the relationship between student attachment and student adjustment.